2016
DOI: 10.11138/mltj/2016.6.1.097
|View full text |Cite
|
Sign up to set email alerts
|

Previous physical exercise slows down the complications from experimental diabetes in the calcaneal tendon

Abstract: SummaryBackground: the complications caused by diabetes increase fragility in the muscle-tendon system, resulting in degeneration and easier rupture. To avoid this issue, therapies that increase the metabolism of glucose by the body, with physical activity, have been used after the confirmation of diabetes. We evaluate the biomechanical behavior of the calcaneal tendon and the metabolic parameters in rats induced to experimental diabetes and submitted to pre-and post-induction exercise. Methods: 54-male-Wistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Non-enzymatic glycation was probably the responsible for the increase of this value due to the covalent bonds of advanced glycation agents between collagenous structures 8,9 . Such results corroborate those found in other studies that showed an increase in the elastic modulus of the calcaneal tendon of rabbits undergoing non-enzymatic glycation 28 and Wistar rats induced to diabetes mellitus 29 . The decrease of elastic modulus to normal levels in diabetic animals subjected to resistance training demonstrated the restoration of the viscoelastic capability of the tendon, resulting from jump training in an aquatic environment.…”
Section: Discussionsupporting
confidence: 82%
“…Non-enzymatic glycation was probably the responsible for the increase of this value due to the covalent bonds of advanced glycation agents between collagenous structures 8,9 . Such results corroborate those found in other studies that showed an increase in the elastic modulus of the calcaneal tendon of rabbits undergoing non-enzymatic glycation 28 and Wistar rats induced to diabetes mellitus 29 . The decrease of elastic modulus to normal levels in diabetic animals subjected to resistance training demonstrated the restoration of the viscoelastic capability of the tendon, resulting from jump training in an aquatic environment.…”
Section: Discussionsupporting
confidence: 82%
“…However, except for the decrease in the elastic modulus, de Oliveira et al [ 25 , 26 ] showed increases in specific strain, maximum strain, and energy/tendon areas in diabetic tendons compared with nondiabetic tendons. Bezerra et al [ 27 ] reported increases in the elastic modulus and maximum tension of diabetic tendons. In addition to the ultimate stress and modulus in diabetic tendons at the material level, the nanoscale modulus of tendon fibrils was also significantly higher and more variable than that of nondiabetic tendons[ 28 ].…”
Section: Changes In Biomechanical Properties In Diabetic Tendinopathymentioning
confidence: 99%
“…Different modalities of laser photobiomulation (LPBM) therapy [1012] and physical activity [1315] have been used to improve normal and diabetic tendon healing in animals and humans. LPBM, for instance, has been demonstrated to modulate inflammation and reduce edema in tendon healing [16,17] in addition to alter gene expression of several MMPs in diabetic wounds and to enhance collagen production [18].…”
Section: Introductionmentioning
confidence: 99%
“…LPBM, for instance, has been demonstrated to modulate inflammation and reduce edema in tendon healing [16,17] in addition to alter gene expression of several MMPs in diabetic wounds and to enhance collagen production [18]. On the other hand, moderate aerobic exercise has been shown to attenuate tendinous complications in diabetes [15], restore tendon biomechanical properties [14], enhance collagen synthesis and increase the organization of the tendon matrix [19]. However, the underlying mechanisms by which LPBM and exercise enhance tendon healing remain to be determined, especially in DM.…”
Section: Introductionmentioning
confidence: 99%